Representation of Graph Theory in Students’ Communication Network at Female Students’ Dormitory of State Islamic Institute of Palopo - Aswad, Muhammad Hajarul; Husain, Wahyuni (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2016)
The application of Graph Theory Concept in Communication Network Analysis is interesting to observe. This research was carried out to learn how Communication Network structure was formed and who had necessary role in the network. It was explorative research and conducted at Female Students’ Dormitory of State Islamic Institute of Palopo (Asrama Putri IAIN Palopo). The results were interpreted by using Microsoft NodeXL Version 1.0.1.113. It was found that the communication network structure of female students’ who stayed at the Dormitory decentralized. It shows that each student had same opportunity to communicate one another directly or indirectly, which 4 to 9 path distance. It was also identified that from 110 people, Suarni was the student who had significant influence in the communication network.